Effects of hypoglycemia on myocardial susceptibility to ischemia–reperfusion injury and preconditioning in hearts from rats with and without type 2 diabetes - Pælestik, Kim B. (Cardiovasc Diabetol, 2017)
BACKGROUND: Hypoglycemia is associated with increased mortality rate in patients with diabetes. The underlying mechanisms may involve reduced myocardial tolerance to ischemia and reperfusion (IR) or reduced capacity for ischemic preconditioning (IPC). As IPC is associated with increased myocardial glucose uptake (MGU) during reperfusion, cardioprotection is linked to glucose metabolism possibly by O-linked β-N-acetylglucosamine (O-GlcNAc). We aimed to investigate the impact of hypoglycemia in hearts from animals with diabetes on myocardial IR tolerance, on the efficacy of IPC and whether modulations of MGU and O-GlcNAc levels are involved in the underlying mechanisms. METHODS: In a Langendorff model using diabetic ZDF (fa/fa) and non-diabetic (fa/+) rats (n = 6–7 in each group) infarct size (IS) was evaluated after 40 min of global ischemia and 120 min reperfusion during hypoglycemia [(glucose) = 3 mmol/l] and normoglycemia [(glucose) = 11 mmol/l]. Myocardial glucose uptake and O-GlcNAc levels were evaluated during reperfusion. IPC was induced by 2 × 5 min of global ischemia prior to index ischemia. RESULTS: IS increased in hearts from animals with (p < 0.01) and without (p < 0.01) diabetes during hypoglycemia compared to normoglycemia. IPC reduced IS during normoglycemia in both animals with (p < 0.01) and without (p < 0.01) diabetes. During hypoglycemia, however, IPC only reduced IS in hearts from animals with diabetes (p < 0.05). IPC increased MGU during reperfusion and O-GlcNAc levels in animals with diabetes during hypo- (MGU: p < 0.05, O-GlcNAc: p < 0.05) and normoglycemia (MGU: p < 0.01, O-GlcNAc: p < 0.05) and in animals without diabetes only during normoglycemia (MGU: p < 0.05, O-GlcNAc: p < 0.01). CONCLUSIONS: Hypoglycemia increases myocardial susceptibility to IR injury in hearts from animals with and without diabetes. In contrast to hearts from animals without diabetes, the hearts from animals with diabetes are amenable to cardioprotection during hypoglycemia. In parallel with IPC induced cardioprotection, MGU and O-GlcNAc levels increase suggesting that increased MGU and O-GlcNAc levels are involved in the mechanisms of IPC.